The Swiss PET system and similar programs in Germany and Austria - Barabasch, Antje [Verfasser]; Heller, Naomi [Verfasser] (My University, 2020)
"Professional education and training play an increasing role in the education system, because young adults expect to continue their education beyond their initial vocational education and training (VET). Being able to professionally reorient oneself or upgrade one's know-how in order to improve career opportunities is not only a question of the attractiveness of VET, but also a condition for employers who need a workforce with upgraded skills. Switzerland, Austria and Germany have all created their own approaches to further VET-based education (at postsecondary and tertiary level), that are somewhat similar, but also different in many respects. Considering the European trend of increasing 'academisation' it seems important to understand which other pathways to higher qualifications and accordingly jobs with more responsibilities exist and how they compare and contrast to each other. This book chapter presents a description of the different approaches to professional (or further) VET education in the three countries and compares them. Particular attention is paid to the structure and role of school-based tertiary education and professional examinations taking Switzerland as the country of reference for this comparison." (author's abstract ; BIBB-Doku)
Keywords: T 1.5 International vergleichende Berufsbildungsforschung; I 2.2.1 Westeuropa; I 2.1 Deutschland; Vergleichende Berufsbildungsforschung; Berufsbildungssystem; Höhere Berufsbildung; Aufstiegsfortbildung; Akademisierung; Schweiz; Österreich; Bundesrepublik Deutschland